From Acupuncture to Interaction between δ-Opioid Receptors and Na+ Channels: A Potential Pathway to Inhibit Epileptic Hyperexcitability. (3rd April 2013) - Chao, Dongman; Shen, Xueyong; Xia, Ying
Abstract : Epilepsy is one of the most common neurological disorders affecting about 1% of population. Although the precise mechanism of its pathophysiological changes in the brain is unknown, epilepsy has been recognized as a disorder of brain excitability characterized by recurrent unprovoked seizures that result from the abnormal, excessive, and synchronous activity of clusters of nerve cells in the brain. Currently available therapies, including medical, surgical, and other strategies, such as ketogenic diet and vagus nerve stimulation, are symptomatic with their own limitations and complications. Seeking new strategies to cure this serious disorder still poses a big challenge to the field of medicine. Our recent studies suggest that acupuncture may exert its antiepileptic effects by normalizing the disrupted neuronal and network excitability through several mechanisms, including lowering the overexcited neuronal activity, enhancing the inhibitory system, and attenuating the excitatory system in the brain via regulation of the interaction between δ -opioid receptors (DOR) and Na + channels. This paper reviews the progress in this field and summarizes new knowledge based on our work and those of others.